STUDI PENGGUNAAN PASIR DHARMASRAYA DAN PENAMBAHAN CANGKANG SAWIT SEBAGAI AGREGAT KASAR TERHADAP KUAT TEKAN BETON NORMAL - Arman A; Made Lesmana Gandi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Concrete is a mixture between coarse aggregate, fine aggregate, cement and water. Pembuatan beton normal diinovasikan denganusing Dharmasraya sand and palm shell as a coarse aggregate against the strength of normal concrete press. Palm shell waste is mostly used as an alternative fossil replacement energy commonly used as fuel in steam power plants, and Dareh River is a river where it is made into gold and sand mines and this research is experimental which is carried out in the laboratory of Padang Institute of Technology and UPTD Laboratory of construction materials of the Public Works Office of West Sumatra Province, the object of this research is the minimum quality of concrete K-250 that uses sand from Dharmasraya and palm shells. The average concrete press strength result at the age of 3 days.from the use of mixtures for normal concrete with an average press strength of 207 kg / cm2, from the use of mixtures for concrete with an additional 2.5% palm shell obtained an average press strength yield of 163 kg / cm2, from the use of mixtures for concrete with an additional 5% palm shell obtained an average press strength yield of 136.3 kg / cm2, fromthe use of mixtures for concrete with an additional 7.5% palm shell obtained an average press strength yield of 146 kg / cm2. While at the age of 28 days, from the use of mixtures for normal concrete obtained an average press strength yield of 307.3 kg/cm2 with an additional 2.5% palm shell obtained an average press strength yield of 308 kg/cm2,fromthe use of mixtures for concrete with an additional 5 % of palm shell obtained an average press strength of 331.3 kg/cm2, from the use of mixtures for concrete with an additional 7.5% palm shell obtained an average press strength yield of 239.3 kg / cm2.Keywords: Palm Shell, Strong Press Normal Concrete, Dharmasraya Sand.